A matched case-control study of the prognosis of early breast cancer in patients with Li-Fraumeni syndrome (BREAST TP53). (April 2023) - Petry, Vanessa; Bonadio, Renata Colombo; Testa, Laura; Cohn, Daniela JBH.; Cagnacci, Allyne; Campos, Roberta G.; Fragoso, Maria Cândida Bv; Estevez-Diz, Maria del Pilar
Abstract: Introduction: Breast cancer (BC) is the most common type of cancer in premenopausal women with germline TP53 pathogenic variants (mTP53) (Li Fraumeni syndrome - LFS). However, little is known about the BC prognosis in these patients. This study analyzed the BC-related oncologic outcomes of patients with LFS. Methods: We evaluated a cohort of LFS patients with BC in comparison with a control cohort of BC patients with no pathogenic variant in a hereditary cancer panel. The primary endpoint was recurrence-free survival (RFS). Due to the risk of second malignancies in LFS, only locoregional and distant recurrences were considered events for RFS. Secondary endpoints included rates of contralateral BC, overall survival (OS), and breast cancer-specific survival (BCSS). Results: Forty-one patients were evaluated in the mTP53 group and 82 in the control group. Median age at BC diagnosis was 40 and 41 years, respectively. The mTP53 group received less adjuvant radiotherapy than the control group (63.4% vs 93.9%, P < 0.001). Other relevant baseline characteristics and treatment received were similar between groups. 5y-RFS rates were 79.4% in the mTP53 versus 93.6% in the control group (HR 2.43, 95%CI 0.74–8.01, P = 0.143); and were not impacted by the use of adjuvant radiotherapy. 5y-BCSS rates were 92.2% and 98.6%, respectively (HR 1.87, IC95% 0.25–13.48, P = 0.534). Conclusions: Our results showed no statistically significant difference in BC-related RFS and BCSS between patients with mTP53 and a control group with no pathogenic variant. Larger multicentric studies are warranted to confirm these results. Highlights: Women with Li Fraumeni syndrome (LFS) have a high risk of breast cancer (BC). BC in LFS is frequently estrogen receptor-positive and HER2-positive. Nevertheless, little is known about BC behavior and prognosis in these patients. We evaluated BC-related outcomes in LFS, including recurrence-free survival (RFS). 5-year RFS was 79% in the LFS group and 93% in a matched control group (P = 0.143).